Increase Family Knowledge of Lung Tuberculosis Prevention Attitudes - M. Iqbal Alfarizi; Ricky Riyanto Iksan; Sri Atun Wahyuningsih (Comprehensive Health Care, 2021)
Pulmonary Tuberculosis is one of the problems that cause the biggest death after cardiovascular disease and respiratory disease number one from group one of the infectious disease group which is still an unresolved problem in the world, even in Indonesia. This study aims to identify the effect of knowledge and attitudes on the prevention of pulmonary tuberculosis transmission in the family. The method used is Case Study Design starting from the data collection stage, namely Case Study is a form of research from a problem that has specific characteristics with individual, family, or group targets, even the wider community. The results showed that after giving health education, there was an increase in the level of knowledge and attitude of prevention efforts in the Pretest and Posttest scores. The level of family knowledge is good at 75%, while 25% is still vulnerable to lack of knowledge. Then for the attitude of prevention efforts obtained 100% data in good prevention efforts. In conclusion, the better the level of knowledge, the better the prevention of Tuberculosis in the family of the Community Health Center in Slipi Village.